Pilottar: a multi-user augmented reality card game - Δεληγιάννης, Κωνσταντίνος (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή Εφαρμοσμένων Τεχνών και Επικοινωνίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Nowadays, the use of Augmented Reality technologies is rapidly growing. Using Augmented Reality we can inject virtual data and objects into the real physical environment enhancing collaboration and interaction. Moreover, mobile devices were also advanced with high computing and graphical processors. This enhancement allowed AR technology that needs high computing calculations to be expanded on mobile devices increasing its portability factor. This research thesis investigates Augmented Reality technology applied in mobile games. Furthermore, an AR card game was developed to examine the realistic aspect of the technology. Also, this AR game supports multiple users investigating as well the networking inside this technology. The aim of this project was to discover whether such an AR game can replace the traditional game. The procedure used for developing the game is explained in detail. After developing the game, an evaluation was conducted. Investigation results are outlined and the findings are discussed. Finally, future development expansion and corrections are described.
Keywords: Augmented Reality technologies; mobile games